The Southern Extension and Reactivations of the Clarendon-Linden Fault System - Jacobi, Robert; Fountain, John (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1993)
ABSTRACTGas seeps located near Pike, New York, on the inferred location of the central fault of the Clarendon-Linden Fault System (CLF), were initiated during, or slightly after, the Saguenay earthquake, 1988. Analyses of the gas show that the gas seeps have a Devonian shale source, and a nearby well suggests that the source may be as deep as 330 m. Thus, CLF fractures extending to depths possibly as great as 300+ m were probably opened as a local response to the Saguenay event, allowing the gas to be vented. Published data show that the CLF extends from Lake Ontario to slightly south of Pike. Previously, there were insufficient data available to enable investigators to determine if the fault system continued farther south. Our soil gas survey and analyses of well logs indicate the CLF continues south into Allegany County, which borders the state of Pennsylvania. Closely-spaced wells suggest that the central fault of the CLF is probably a series of step faults, even in units above the Silurian evaporite section, although a monocline cannot be ruled out. Growth-fault geometries of the CLF suggest that the CLF experienced motion during the Taconic and Acadian orogenies. Isopach maps, coupled with the proposed southward extrapolation of the CLF, suggest that in Late Devonian times the CLF motion history recorded the passage of the Appalachian foreland basin axis across the CLF.